TALENT SEGMENTATION: DOES IT AFFECT COMMITMENT? A STUDY IN IT INDUSTRY, CHENNAI - Krishnan, K; Kalra, Alka (PEOPLE: International Journal of Social Sciences, 2017)
The Talent Management is the sound and incorporated human asset rehearses with the destinations of pulling in and holding the ideal people, for the correct positions, at the opportune time. The outcomes demonstrate that there is noteworthy distinction between socio-economic features of critical employees and preference of talent management practices in IT companies. Critical employees show a high level of commitment in exclusive segmentation and low level of commitment in inclusive segmentation. The outcome also demonstrates that, Non-Critical employees show a low level of commitment in exclusive segmentation and high level of commitment in inclusive segmentation.